2017
DOI: 10.4103/ijmpo.ijmpo_33_16
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal mass: Unusual presentation and outcome

Abstract: Aim:Adrenal mass may be functioning or nonfunctioning with varied clinical presentations. This study aimed to report the nature and management of uncommon adrenal mass and to review literature.Materials and Methods:This was an retrospective observational analysis of children with uncommon adrenal mass admitted during 2009–2015. Clinical features, investigations, and management of patients were analyzed.Results:Among six, two each were adolescent and neonate, and one each was young infant and prenatal. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“… 8 Previous studies have identified the accuracy of prenatal ultrasound in diagnosing fetal neuroblastoma as 51–70%, adrenal hematoma as 72–86%, and subphrenic pulmonary sequestration as 64–81%. 4 , 9 In the present study, the findings concerning diagnostic accuracy were consistent with those of previous research, with the accuracy of diagnosis of adrenal cyst and subphrenic pulmonary sequestration reaching as high as 85.7%. This indicates that attention should be paid to the value of prenatal ultrasonography as a diagnostic tool.…”
Section: Discussionsupporting
confidence: 92%
“… 8 Previous studies have identified the accuracy of prenatal ultrasound in diagnosing fetal neuroblastoma as 51–70%, adrenal hematoma as 72–86%, and subphrenic pulmonary sequestration as 64–81%. 4 , 9 In the present study, the findings concerning diagnostic accuracy were consistent with those of previous research, with the accuracy of diagnosis of adrenal cyst and subphrenic pulmonary sequestration reaching as high as 85.7%. This indicates that attention should be paid to the value of prenatal ultrasonography as a diagnostic tool.…”
Section: Discussionsupporting
confidence: 92%
“…Management of adrenal or suprarenal cysts is largely by surgical excision to exclude malignancy, as enumerated in an American study, where they reviewed 613 cases, including those they had managed, where they found that only 7% of their cases were malignant or potentially malignant, with only 1 reported malignancy, and concluded that aspiration of the cysts may be done 6 in mind when assessing these patients are benign and malignant lesions like adrenal or suprarenal masses e.g., adenocarcinomas or pheochromocytomas 9 . Other rare lesions identified in case reviews include adrenal angiolipoma as possible differential diagnosis 17 , as well as a mucinous cystic neoplasm 11 , and an unusual prenatal diagnosis of an adrenal cyst in pregnancy which had to be excised at laparotomy while the pregnancy was carried to term delivery 12,13,16 . Possibility of the diagnosis of congenital adrenal teratomas should also be borne in mind when examining neonates 14 , as well as a congenital adrenal cystic neuroblastoma 16 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…When they do, they are often non-specific symptoms, for example respiratory symptoms as highlighted in our case study 4 , left testicular discomfort as identified by a case report in the United Kingdom 8 and epigastric pain and abdominal distension 15 . An Indian case report even reported unusual presentations of hypertensive retinopathy, virilization and bleeding diathesis 17 .…”
Section: Introductionmentioning
confidence: 99%